2018
DOI: 10.2214/ajr.17.19103
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Intermediate-Delay Washout CT Images for Differentiation of Malignant and Benign Adrenal Lesions: A Multivariate Analysis

Abstract: OBJECTIVE. The objective of this study was to identify features that impact the diagnostic performance of intermediate-delay washout CT for distinguishing malignant from benign adrenal lesions. MATERIALS AND METHODS. This retrospective study evaluated 127 pathologically proven adrenal lesions (82 malignant, 45 benign) in 126 patients who had undergone portal venous phase and intermediate-delay washout CT (1–3 minutes after portal venous phase) with or without unenhanced images. Unenhanced images were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]). We introduced a new imaging parameter of relative enhancement ratio by combining unenhanced attenuation and absolute enhancement, yielding a diagnostic performance almost comparable with the previously reported washout CT (sensitivity, 86% vs 82%-92%; specificity, 95% vs 87%-100%) for the discrimination of lipid-poor adenomas (5,9,10,21).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]). We introduced a new imaging parameter of relative enhancement ratio by combining unenhanced attenuation and absolute enhancement, yielding a diagnostic performance almost comparable with the previously reported washout CT (sensitivity, 86% vs 82%-92%; specificity, 95% vs 87%-100%) for the discrimination of lipid-poor adenomas (5,9,10,21).…”
Section: Discussionsupporting
confidence: 84%
“…A total of 29 relevant articles from the literature were reviewed (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(14)(15)(16)19,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Sixteen studies provided data on both adenomas (n = 964) and nonadenomas mostly comprising metastases (n = 623), all of which showed higher absolute enhancement in adenomas than in nonadenomas (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Flexible for actual applications, our modelling framework facilitates pattern identification with analyses of cohorts with heterogeneous lesion sizes. Our unsupervised Bayesian model is applied to identify textural patterns intrinsic to adrenal lesions with CT. Data were obtained in a retrospective study of patients who underwent concordant biopsy and imaging based on a dynamic sequence of CT scans with and without administration of contrast (Ng et al., 2018a,b,c). To elucidate whether textural subtypes identified exhibit pathological orientation, subtypes are evaluated for correspondence with each lesion’s diagnosed pathological status.…”
Section: Introductionmentioning
confidence: 99%